3D laserový profilometr jako senzor dat pro digitální dvojčata - Gabriel, Michal; Michal Gabriel (České vysoké učení technické v Praze, 2020)
Bakalářská práce se zabývá realizací dema 3D skeneru, za použití profilometru LLT 2800-25. Součástí je kalibrace a ověření přesnosti skeneru. Ovládání skeneru je implementováno v jazyce Python. Dále se teoreticky zabývá problematikou využití 3D skeneru v rámci digitálního dvojčete.

This bachelor thesis focuses on creation of 3D scanner demo with the use of profile sensor LLT 2880-25. Included is the calibration and evaluation of the scanner accuracy. The control application is programmed in Python language. Additionally thesis theoretically explores the use of 3D scanners in the context of digital twins.
3D Laser Profilometer as a Digital-twins Sensor
Keywords: 3D skener; laserový profilometr; průmysl 4.0; triangulační skener; digitální dvojče; 3D scanner; laser scanner; industry 4.0; triangulation scanner; digital twin